A bottom-up method for remixing narratives for virtual heritage experiences. (December 2022) - Basaraba, Nicole
Considering the impacts COVID-19 has had on travel and many economies, developing virtual experiences that are well-received by different publics has become even more prominent. This paper shows how a multimodal discourse analysis can be used to as a bottom-up approach to identifying narrative themes that can be used in virtual experiences for cultural heritage sites. A case study on 11 UNESCO World Heritage Australian Convict Sites shows how diverse sources of user-generated content, tourism marketing materials and historical information can be analysed and then remixed into a virtual tour of the sites in the form of an interactive web documentary (iDoc). Although this case study involved a total of seven narrative development phases, this paper focuses on two phases, namely how the user model and content model were determined. These models were later used to develop the resulting iDoc prototype. The user model focused on the prospective audience of cultural heritage tourists, and a content model of narrative themes for the iDoc was developed through a multimodal discourse analysis. This bottom-up approach of analysing existing cultural data allows for the discovery of the prospective audiences' interests as well as narrative themes that can be included in virtual heritage experiences. It also provides a new creative methodology that can prevent issues that may arise with top-down narratives that focus too heavily on one institutional perspective or national narrative and lack direct engagement with or understanding of today's publics.